Expressing Uncertainty in Dental Age Estimation: A Comparison between Two Methods of Calculating the "Average" Standard Deviation. Issue 5 (1st April 2019) - Draft, Derek; Lucas, Victoria S.; McDonald, Fraser; Andiappan, Manoharan; Roberts, Graham
Abstract: The expression of uncertainty is defined by the standard deviation and is usually expressed in multiples of the standard deviation (±1sd, ±2sd, and ±3sd). The objective was to use weighting of the sd calculation by the number or count of subjects for each tooth development stage. A comparison shows the difference between the range of uncertainty using the unweighted sd and the weighted sd. The range of uncertainty related to Dental Age Estimation is statistically significantly greater ( p  < 0.001) for the weighted sd compared to the unweighted sd. It is concluded that the number of subjects for each Tooth Development Stage in the Reference Data set should be included in the calculation for a single Dental Age Estimation using the Simple Average Method when presenting the uncertainty associated with the point estimate of the "mean" for Dental Age Estimation of a single subject of unknown age.